Vladimir Kozák, as câmeras e os Xetá - Paula Grazielle Viana dos Reis (2014)
The Xeta, amerindians of south american lowlands, were targeted in the genocide and ethnocide in the decade 1940 to 1950 during the period that corresponds with the first contacts with agricultural projects on the left bank of the river Ivai tributary of the Parana river. In this context the drastic depopulation, a massive production of photographic and cinematic images was made by Vladimir Kozak for scientific purposes. This study consists of: (i) description of the films and photographs made by Vladimir Kozak between Xeta (1955-1976) as a means and object of study; (ii) uses this material in anthropological research; (iii) ontological analysis of the images woven with themes and theories present in research on Xeta and Tupi-Guarani; (iv) notes Xetagenocide and ecological disaster.